ANALISIS AKUNTABILITAS, PERAN PERANGKAT DESA, TRANSPARANSI TERHADAP PENGELOLAAN DANA DESA - Nur Fauziah, Binti; Astuti, Puji; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
Abstract To analyze the accountability, role of village officials, and transparency towards village fund management, either individually (partially) or jointly (simultaneously) the purpose of this study. A quantitative approach was applied in this study to collect data using surveys that were distributed throughout Pace District, Nganjuk Regency. The data analysis method uses multiple linear analysis techniques. The purposive sampling technique is used as a sample taken with certain criteria so that a sample of ninety people is obtained. The results of this study state that (1) Accountability partially affects village fund management, (2) the role of village officials partially does not affect village fund management, and (3) transparency partially affects village fund management. (4) Together accountability, the role of village officials and transparency affect the management of village funds. In managing village funds, it is hoped that government employees must implement the principles of accountability and transparency in it in order to realize the principles of good government in its implementation.